If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2y + 1) + -7y = 18 Reorder the terms: 4(1 + 2y) + -7y = 18 (1 * 4 + 2y * 4) + -7y = 18 (4 + 8y) + -7y = 18 Combine like terms: 8y + -7y = 1y 4 + 1y = 18 Solving 4 + 1y = 18 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 1y = 18 + -4 Combine like terms: 4 + -4 = 0 0 + 1y = 18 + -4 1y = 18 + -4 Combine like terms: 18 + -4 = 14 1y = 14 Divide each side by '1'. y = 14 Simplifying y = 14
| 84=6(1+3r)+6 | | 164=-8(1-5n)+3n | | log(12x)-log(2x)+log(3x)=log(8x)+log(9)+log(12) | | y=3e-25x+16e-32 | | 101=-8(X-3)-3x | | 34=x+x+(x-2) | | t/5-7=13 | | 5p-2q=23 | | 3(4s+4)=7 | | 4/3x3.14x343= | | 6(2l+2)=132 | | -1+3(7+3x)=83 | | 7m-3+2m=13+m | | sinx=1.5 | | 13x+5y=179 | | 25=40+3x | | 6(21+2)=132 | | 144=6(5x+4) | | 15x+7y=193 | | 3(a-2)=60 | | -88=2x-5(-2x+8) | | -4(8x-8)=192 | | (q-4)*7=-24 | | 3(x+1)+7=6(x+1)+63 | | 6+29=27+6+2 | | -92=7+3(4r-5) | | 550=(x-.05x) | | 10x+13y=11 | | -12+=16 | | 6(-7b-5)-5=-371 | | ad=8 | | 3D+5D= |